2010
DOI: 10.1124/jpet.110.169276
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Interactions between Mu-Opioid Receptor Agonists and the Serotonin Uptake Inhibitor Clomipramine in Rhesus Monkeys: Role of Mu Agonist Efficacy

Abstract: Mu-opioid agonists are effective analgesics but have undesirable effects such as sedation and abuse liability that limit their clinical effectiveness. Serotonergic systems also modulate nociception, and serotonin uptake inhibitors may be useful as adjuncts to enhance analgesic effects and/or attenuate undesirable effects of mu agonists. This study examined the effects of the serotonin uptake inhibitor clomipramine on behavioral effects produced in rhesus monkeys by mu agonists with varying efficacy at mu recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 36 publications
(68 reference statements)
8
30
0
Order By: Relevance
“…This difference between methadone and morphine may be related to their different efficacies as mu agonists. Specifically, morphine has lower efficacy than methadone as a mu agonist (Selley et al, 1998), and this lower efficacy results in both shallower dose-effect curves and greater potency differences for production of different effects (e.g., Banks et al, 2010). Consequently, use of morphine may have facilitated detection of mu agonist-induced increases in cocaine choice at doses that did not eliminate responding or produce other dose-limiting side effects.…”
Section: Discussionmentioning
confidence: 99%
“…This difference between methadone and morphine may be related to their different efficacies as mu agonists. Specifically, morphine has lower efficacy than methadone as a mu agonist (Selley et al, 1998), and this lower efficacy results in both shallower dose-effect curves and greater potency differences for production of different effects (e.g., Banks et al, 2010). Consequently, use of morphine may have facilitated detection of mu agonist-induced increases in cocaine choice at doses that did not eliminate responding or produce other dose-limiting side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The following are among the adjuncts that have been demonstrated to selectively enhance m-opioid antinociception over rate suppression: selective serotonin uptake inhibitors (Gatch et al, 1998;Banks et al, 2010), a d-opioid receptor agonist (Stevenson et al, 2003), an N-Methyl-Daspartate antagonist (Fischer and Dykstra, 2006), metabotropic glutamate receptor 1 and metabotropic glutamate receptor 2/3 antagonists (Fischer et al, 2008), and cannabinoids (Maguire and France, 2014). Interestingly, in some cases, greater antinociceptive enhancement of low-compared to high-efficacy m agonists was reported (Gatch et al, 1998;Banks et al, 2010), whereas in other cases, the opposite was found (Maguire and France, 2014). These studies represent promising potential novel pain therapies; however, subsequent clinical testing of these therapies has not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that drugs acting on 5-HT systems might be particularly useful for treating pain when they are used in combination with opioids. For example, the SSRIs fluoxetine and clomipramine potentiate the antinociceptive effects of morphine in rats and rhesus monkeys (Larson and Takemori 1977; Hynes et al 1985; Gatch et al 1998; Banks et al 2010), and the 5-HT releaser fenfluramine increases the antinociceptive effects of morphine in monkeys (Li et al 2011) and the analgesic effects of morphine in humans (Coda et al 1993). Agonists acting selectively on 5-HT receptor subtypes have also been shown to enhance the antinociceptive effects of opioids.…”
mentioning
confidence: 99%